2004
DOI: 10.1007/s11199-004-0719-9
|View full text |Cite
|
Sign up to set email alerts
|

Are Doors Being Opened for the “Ladies’’ of College Sports? A Covariance Analysis

Abstract: The purpose of this study was to examine sports symbols of colleges and universities for evidence of sexism and to identify factors that differentiated schools with and without sexist nicknames for their athletic teams. Data on team names and eight measures of women's athleticism were collected from 112 colleges and universities for the 2000-2001 academic year. MANCOVA results revealed that women's athleticism was stronger at schools with nonsexist nicknames for seven of the eight measures, although only one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The second most common form of sexist naming found by Eitzen and Baca Zinn (1989) and the most common form found by Ward (2004) was the use of the feminine qualifier lady in the name for women's teams. The term lady was used in several ways.…”
Section: Sexist Naming Intersecting Inequalities and Sportsmentioning
confidence: 99%
See 3 more Smart Citations
“…The second most common form of sexist naming found by Eitzen and Baca Zinn (1989) and the most common form found by Ward (2004) was the use of the feminine qualifier lady in the name for women's teams. The term lady was used in several ways.…”
Section: Sexist Naming Intersecting Inequalities and Sportsmentioning
confidence: 99%
“…The independent variables used in the logistic and OLS regression analyses consist of institutional and athletics department characteristics that were previously found to be important determinants of gender equity in collegiate athletics (Anderson et al 2006;Ward 2004). In the logistic regression analysis of sexist naming practices, the independent variables consist of the following: size of the institution, religious affiliation, private status, the designation as a historically black college or university (HBCU), tuition and fees charged, athletic league and division membership, presence of a men's football program, gender of the head coach of the women's basketball team, and the climate for women in the athletics department (measured as the percentage of female coaches employed by the athletics department).…”
Section: Independent Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Although the evidence is mixed (Weinberg, Reveles, and Jackson, 1984; Frankl and Babbitt, 1998), some have suggested that women athletes themselves prefer to be coached by men and that this preference in turn influences athletic administrators. It follows that southern conservatism on a variety of gender‐related issues could contribute to a dearth of women coaches (Ward, 2004:704). Whereas more traditional gender‐role orientations are also more likely to dominate in religious institutions, public institutions might be subject to pronounced internal and external pressures toward openness to gender equality, for both legal and political reasons.…”
Section: Explaining the Decline In The Proportion Of Women Coachesmentioning
confidence: 99%